The intramolecular Diels-Alder vinylthiophen (IMDAV) reaction: An easy approach to thieno[2, 3-f]isoindole-4-carboxylic acids. Issue 43 (25th October 2017) - Horak, Yuriy I.; Lytvyn, Roman Z.; Laba, Yevhen-Oleh V.; Homza, Yuriy V.; Zaytsev, Vladimir P.; Nadirova, Maryana A.; Nikanorova, Tatiana V.; Zubkov, Fedor I.; Varlamov, Alexey V.; Obushak, Mykola D.
Graphical abstract: Highlights: Application of the IMDAV strategy in synthesis of thieno[2, 3- f ]isoindoles. Mild and diastereoselective synthesis of thieno[2, 3- f ]isoindole-4-carboxylic acids. Reaction of 3-thienylallylamines with maleic anhydride gives thieno[2, 3- f ]isoindoles. Abstract: The reaction of readily accessible 3-(thien-2-yl)allylamines with maleic anhydride, followed by a domino sequence involving successive acylation/[4+2] cycloaddition steps, leads to the formation of the thieno[2, 3- f ]isoindole core. The key step, the intramolecular Diels-Alder vinylaren (IMDAV) reaction, proceeds with high level of diastereoselectivity and with formation of a single diastereoisomer of the target product 4, 4a, 5, 6, 7, 7a-hexahydro-3a H -thieno[2, 3- f ]isoindole-4-carboxylic acids in excellent yields. If the reaction is carried out at room temperature, it occurs in 2–3 days and the proton migration ( H -shift) does not take place at the last stage. In boiling benzene, the reaction is complete after three hours, but in this case a slight impurity of byproducts bearing aromatic thiophene ring – 4a, 5, 6, 7, 7a, 8-hexahydro-4 H -thieno[2, 3- f ]isoindole-4-carboxylic acids is formed.